Relationship between variables and anemia status among female workers - Purbowati; Nurohmi Susi; Widyan Aisya Rizki (BIO Web of Conferences)
One of the micronutrient problems that becomes a worldwide concern, including Indonesia, is iron deficiency anemia. Anemia status in workers can result in reduction of health and work productivity. This study examines anemia status and factors associated with anemia in female workers. The research was conducted among 343 female production workers at a cigarette company in Kudus Regency, Central Java, Indonesia. The variables were hemoglobin levels, age, BMI, MUAC, energy and protein intake, and caffeine consumption. Instruments used include an Easy touch Hb test to check hemoglobin levels, weight scales, and microtoise for body height to calculate BMI, MUAC measuring tapes, Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) in a month for determining energy, protein, and caffeine intake. The results showed that 141 subjects (41.1%) experienced anemia, including 59 mild, 73 moderate, and 9 severe anemia. Factors related to anemia status among female workers include age, energy adequacy, protein adequacy, and caffeine consumption. Meanwhile, BMI and MUAC variables were not related to anemia status. Risk factors for anemia in women under 50 years of age include adequate/excessive energy intake, adequate protein deficit, and caffeine consumption of more than two glasses per day.